Hubungan Pengetahuan Remaja Tentang Vulva Hygiene dengan Kejadian Keputihan pada Remaja Putri di SMAN 02 Kota Bengkulu - Eka Tulhikmal; Yatri Hilinti; Danur Azissah (LPPJPHKI Universitas Dehasen Bengkulu, 2026)
Vaginal discharge is a common reproductive health problem among adolescent girls. In Indonesia, approximately 75% of women experience vaginal discharge at least once in their lifetime, with some experiencing it during adolescence. The occurrence of vaginal discharge can be influenced by the level of knowledge about vulvar hygiene. A lack of knowledge regarding proper feminine hygiene practices can increase the risk of vaginal discharge. This study aimed to determine the relationship between adolescents’ knowledge of vulvar hygiene and the occurrence of vaginal discharge among female students at SMAN 02 of Bengkulu City. The research employed a descriptive analytic method with a cross-sectional approach. Data were collected through questionnaires distributed to 83 respondents at SMAN 02 of Bengkulu City using a proportionate stratified random sampling technique. The results showed that the majority of respondents (88%) had good knowledge of vulvar hygiene, and almost all respondents (98.8%) did not experience vaginal discharge. The Chi-square statistical test produced a p-value of 0.039 (p < 0.05), indicating a significant relationship between adolescents’ knowledge of vulvar hygiene and the occurrence of vaginal discharge among female students at SMAN 02 of Bengkulu City. Based on these findings, it is recommended that schools enhance reproductive health education through counseling or adolescent health programs, particularly concerning the importance of maintaining feminine hygiene